Finding my way home: assessing home range and habitat selection of reintroduced roe deer (Capreolus capreolus) in central Portugal - Correia, Diogo Alexandre Madeira (2024)
Dissertação de Mestrado em Ecologia apresentada à Faculdade de Ciências e Tecnologia